2009
DOI: 10.1002/nau.20621
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between urodynamic function and 3D cat scan anatomy in neobladders: Does it exist?

Abstract: The study seems to show no significant anatomical or functional difference among the three different types of neobladders. A possible correlation between the position of the neobladder and urinary incontinence is suggested, recognizing further study in a larger population is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
(9 reference statements)
2
7
0
Order By: Relevance
“…Once the posterior plate is created robotically, it is rotated anticlockwise by 908 before urethra-neobladder anastomosis, followed by double cross-folding and true globularization of the neobladder. Our globular robotic iONBs achieved a mean cystometric volume of 514 cm 3 (range 339-1001), which is consistent with mean volumes reported for open ONB series of 430-600 and 450-524 cm 3 for Hautmann [24,25] and Studer [26][27][28] configurations, respectively. Furthermore, the ability to achieve high volumes at low pressure (high compliance) of the robotic iONB lends support to a lowpressure reservoir.…”
Section: Discussionsupporting
confidence: 86%
“…Once the posterior plate is created robotically, it is rotated anticlockwise by 908 before urethra-neobladder anastomosis, followed by double cross-folding and true globularization of the neobladder. Our globular robotic iONBs achieved a mean cystometric volume of 514 cm 3 (range 339-1001), which is consistent with mean volumes reported for open ONB series of 430-600 and 450-524 cm 3 for Hautmann [24,25] and Studer [26][27][28] configurations, respectively. Furthermore, the ability to achieve high volumes at low pressure (high compliance) of the robotic iONB lends support to a lowpressure reservoir.…”
Section: Discussionsupporting
confidence: 86%
“…These results support the hypothesis that a 'stable' neobladder and neobladder neck are important factors for continence in patients with neobladder. Our finding that incontinent patients are characterized by a significantly lower position of the neobladder in the pelvis is in line with the results of Crivellaro et al [16] . Altogether, these results are well in agreement with the integral theory of Petros, according to which pelvic floor integrity is a prerequisite for continence [22] .…”
Section: Discussionsupporting
confidence: 94%
“…One of these studies showed that the location of the neobladder neck in the pelvis has an important impact on voiding: in patients showing good void competence the neobladder neck is located at the most caudal portion of the pouch [17] . Moreover, the position of the neobladder relative to the right femur head showed a linear correlation to continence status [16] . In addition, a wide funneling seems to be necessary for successful micturition [9] .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Comorbidities were reported in eight studies [7,8,13,30,37,53,64,65]. Time of follow-up is reported in 44 (74.6%) studies, but in 15 (23.4%) studies, this data is lacking [7,9,19,23,32,36,39,41,43,46,48,51,53,60,61]. Follow-up ranges from a minimum of 5 months [35] to 179.2 months [31], for a mean value of 42.7 months and a median value of 32.9 (25-75th percentile: 19 to 60.5 months).…”
Section: General Aspectsmentioning
confidence: 99%